ANTIBACTERIAL COMPOSITION AND METHOD FOR DETERMINING ADMINISTRATION OF SAID ANTIBACTERIAL COMPOSITION TO SUBJECT - ITO Yoshihiro; ISAYAMA Jun; GOJI Hiroshi; MASUDA Kanae; AMAGAI Masayuki; ISHIKAWA Hidefumi; WATANABE Kazuto; AOTO Yoshimasa; KAWASAKI Hiroshi (2025)
Provided are an antibacterial composition including bacteria exhibiting antibacterial properties against bacteria positively correlated with a value of SCORAD indicating the severity of atopic dermatitis, and a method for determining administration of the antibacterial composition to a subject. The present invention includes an antibacterial composition including skin resident bacteria as an active ingredient, the antibacterial composition being targeted to inflammation-inducing bacteria (excluding the skin resident bacteria).